Behavior of male and female eclectus parrot (Eclectus roratus) in an artificial environment - Martínez, Eduardo Cesario Araújo; Paz, Vanair Carlos; Navarro, Rodrigo Diana (Acta Scientiarum. Biological Sciences, 2020)
The eclectus parrot (Eclectus roratus) is a species of parrot native to the Solomon Islands, Sumba, New Guinea and nearby islands, northeastern Australia, and the Moluccan Islands. The wide range of behaviors emphasizes the existence of knowledge of only a mere fraction of the significant behavioral parameters of these birds. The objective of this study is to identify the behavior of the eclectus parrot kept in captivity and to check the frequency of these birds in certain places of the nursery, comparing the results to other studies about parrots and the behavior in nature. This is a study about the behavior of a bird with a very pronounced sexual dimorphism, where the males have a predominantly green color, and the females are mainly red-colored. In the wild, while the male perches on the outer branches of the trees, the female usually perches close to tree trunks. This location, together with her red and blue plumage, provides the ideal camouflage in the dark interior of the trees.